Pomegranate-Like Structured Si@SiOx Composites With High-Capacity for Lithium-Ion Batteries - Li, Jianbin; Liu, Wenjing; Qiao, Yingjun; Peng, Gongchang; Ren, Yurong; Xie, Zhengwei; Qu, Meizhen (Frontiers in Chemistry, 2020)
Silicon anodes with an extremely high theoretical specific capacity of 4200 mAh g-1 have been considered as one of the most promising anode materials for next-generation lithium-ion batteries. However, the large volume expansion during lithiation hinders its practical application. In this work, pomegranate-like Si@SiOx composites were prepared using a simple spray drying process, during which silicon nanoparticles reacted with oxygen and generated SiOx on the surface. The thickness of the SiOx layer was tuned by adjusting the drying temperature. In the unique architecture, the SiOx which serves as the protection layer and the void space in pomegranate-like structured could alleviate the volume expansion during repeated lithium insertion/extraction. As a lithium-ion battery anode, pomegranate-like Si@SiOx composites dried at 180 °C delivered a high specific capacity of 1746.5 mAh g-1 after 300 cycles at 500 mA g-1.